Evaluation of vegetables and fish oils for the attenuation of diabetes complications - Parveen, Kehkashan; Siddiqui, Waseem Ahmad; Arif, Jamal Mohammad; Kuddus, Mohammed; Shahid, Syed Monowar Alam; Kausar, Mohd adnan (Cellular and Molecular Biology, 2019)
The present study was accomplished to examine and compare the effect of specific antioxidant-rich oils on hyperglycemia, dyslipidemia, renal function markers and oxidative renal damage in diabetic rats for four weeks. Papaya (P), olive (O), fenugreek (Fe), bitter gourd (B) and fish (Fi) oils were used for this purpose. Streptozotocin (STZ) was injected intraperitoneally in a single dose to induce diabetes. All oils were given orally at a dose of 3g/kg for four weeks in respective group after induction of diabetes. After treatment with oils, blood was collected, and their kidneys were stored. The level of fasting blood glucose (FBG), glycated hemoglobin (HbA1c), total cholesterol (TC), triglycerides (TG), low-density lipoprotein-cholesterol (LDL-C) and very low-density lipoprotein-cholesterol (VLDL-C) increased while amylase and high-density lipoprotein cholesterol (HDL-C) level decreased in the diabetic rats. These changes were augmented by fenugreek, bitter gourd and olive oils treatment. Diabetic rats showed elevated renal function markers in serum, including, serum creatinine (Scr), blood urea nitrogen (BUN) and alkaline phosphatase (ALP), which were restrained significantly by fenugreek and bitter gourd oil treatment. Moreover, fenugreek and bitter gourd oils treatment significantly modulated the level of thiobarbituric reactive substances (TBARS), malonaldehyde (MDA) and catalase (CAT) in the kidney of diabetic rats. The histopathological examination also showed the protective effect of these oils. The study suggests that vegetable oils are effective in reducing hyperglycemia, dyslipidemia and renal damage related to the side effects of diabetes. Thus they may have therapeutic value for preventing diabetes side effects and may be included in oil diet treatment synergically. Thus, our data suggest that oils as potent antidiabetic agent and beneficial in the control of diabetes-related abnormalities such as hyperglycemia, dyslipidemia and renal damage of STZ induced rat model of type 2 diabetes. Our study also supports the suggestion that synergistic possibilities exist concerning the use of these oils in the treatment of diabetes mellitus.